Substance Use among Youth with Currently and Formerly Incarcerated Parents. (2nd January 2017) - Davis, Laurel; Shlafer, Rebecca J.
ABSTRACT: Parental incarceration impacts millions of children in the United States and has important consequences for youths' adjustment. Children of incarcerated parents are at risk for a host of negative psychosocial outcomes, including substance abuse problems. Using data from a statewide survey of youth behavior, the effect of present and past parental incarceration on youths' report of their substance use behaviors was examined. Present and past parental incarceration was significantly associated with use of alcohol, tobacco, marijuana, and prescription drugs, as well as substance abuse and dependence. Implications for practice and research are discussed.